Reaction of arracacha genotypes to the root soft rot caused by Pectobacterium chrysanthemi - Henz, Gilmar Paulo; Reifschneider, Francisco José Becker; Santos, Fausto Francisco dos (Pesquisa Agropecuaria Brasileira, 2005)
The purpose of this paper was to screen thirty-two arracacha genotypes for their reaction to root soft rot. Twenty roots of each genotype were inoculated with two Pectobacterium chrysanthemi isolates in a randomized experiment (10 roots/isolate). After inoculation, roots were individually wrapped with PVC film and kept at 26oC in closed plastic bags. Soft rot lesions were recorded after 36 hours and genotypes were grouped in four classes of susceptibility by cluster analysis: 10 were less susceptible, 16 intermediate, 3 susceptible and 3 very susceptible. All the tested arracacha genotypes showed only variation in the degree of susceptibility.